Type 1 Diabetes and Cytomegalovirus Infection: Cytokine and T Lymphocytes Profile in Pointe Noire, Congo - Atandi Batchy, Aladin; Charley Elenga-Bongo; Luc Magloire Anicet Boumba; Fredy Kibouilou; Freddy Saturnin Pouki; Ben Dorel Kyabaambu; Christ Nkaya Kimpolo; Ghislain Loubano Voumbi; Donatien Moukassa; Exaucé Massengo (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Type 1 Diabetes (T1D) is an autoimmune disease characterized by the destruction of beta cells in the pancreatic islets of Langerhans. This study aimed to investigate the T lymphocyte pathway involved in cytomegalovirus (CMV) infection in T1D patients in the context of. in Pointe Noire Method: We conducted an analytical case-control study over 6 months between June and November 2022. A total of 234 subjects were enrolled, including 68 (T1D +CMV+) cases, 62 (T1D +CMV-) cases, and 104 healthy subjects as the control group (healthy controls). The plasma concentrations of CD4, CD8, CD28, IL2, IL4, and IL10 were measured using ELISA. Linear regression analysis was performed to explore the correlation between T lymphocyte types (CD4, CD8, and CD28) and interleukins. Results: In the case group, the average age was 20.85±0.63 years for (T1D+CMV+) cases, 21.88±4.07 years for (DT1+CMV-) and 31.95±2.13 years for healthy controls. Men were the majority in the study, representing 55.38%, with a male-to-female ratio of 1:2. Plasma concentrations of different types of lymphocytes were higher in the case group compared to the controls CD4 (7,21±0,23 vs 5,71±3,27 vs 2,07±0,14; p<0,0001); CD8 (13,73±0,91 vs 10,01±1,88 vs 1,27±0,14 p <0,0001); CD28 (45.95±2.18 vs 14.39±1.99 vs 7.97±1.96; p<0,0001); IL2 (1048.0±43.47 vs 252.0±10.91 vs 52.91±23.95; p<0,0001); IL4 (474.3±18.45 vs 279.3±169.2 vs 194.9±136.2); IL10 (275.0±134.0 vs 206.0±84.77 vs 44.62±7.22; p <0,0001), and (CD4, CD8, CD28, IL2, IL4, and IL10) showed significant elevation in the case group compared to the controls. The study also revealed a direct correlation between CD4 and CD28. Conclusion: These findings suggest that CMV infection worsens T1D by promoting the increase in CD4, CD8, and CD28 lymphocytes as well as plasma concentrations of interleukins (IL2, IL4, and IL10), and no correlation was observed with CD8.